Jogja Darurat Sampah: Examining the Effectiveness of Zero Inorganic Waste Policy in Various Perspective to Solve Waste Problem in Yogyakarta - Fachrurizal Mahendra Sujono; Fadli Putra Pratama; Nadadistya Fourysa Iksani Putri; Nayla Dhiyaa Izzati; Hani Verdiant; Kafa Abdallah Kafaa (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2024)
Jogja Darurat Sampah represents the urgency of the waste problem due to obstacles in the waste downstream cycle to TPST Piyungan. Waste management policies are identified as ineffective with a reduction in waste transport below 8% until 2022. On 1 January 2023, the Yogyakarta City Government issued the Zero Inorganic Waste Policy as a strategic vision to reduce 15% of downstream waste by 2023. The research aims to evaluate the Zero Inorganic Waste Policy in reconstructing the waste management paradigm of Yogyakarta City. This research applies a case study method by adopting Formative Policy Evaluation. Before the Zero Inorganic Waste policy was issued, the community had a tendency of 'collect-transport-dispose' waste management behaviour. In the context of Evidence-Based Policy Making, this policy was formulated based on evidence of the escalation of waste problems in Yogyakarta City. In the dynamics of policy implementation, there has been a change in 'sort-reduce-reuse-recycle' behaviour in waste management. However, the challenges of misperceptions and community adaptation to the new policy simultaneously emerged. In the formative evaluation framework, the Zero Inorganic Waste policy was evaluated as effective. There was an average decrease in waste haulage of 24% or 56.42 tonnes/day in the first semester of 2023.